Pengaruh Pelatihan Kewirausahaan terhadap Pemberdayaan Ibu Rumah Tangga di Rumah BUMN Kota Tasikmalaya - Muhamad Rizqi Mardiansyah; Nandang Nandang; Nizza Nadya Rachmani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research focuses on analyzing the impact of training programs in empowering housewives who participate in Rumah BUMN Kota Tasikmalaya. The background of this study is the significant poverty conditions in the area and the limited opportunities for housewives to access training and skills development that could improve family welfare. The training program at Rumah BUMN serves as a tangible effort to equip participants with practical skills while creating pathways toward economic independence. This study employed a descriptive quantitative design, with sampling carried out using a saturated sampling technique, meaning that all individuals in the population were included as respondents, involving 65 participants who attended the training as the sample. Data were collected through questionnaires, documentation, and observation, and then analyzed using simple linear regression after fulfilling the classical assumption tests. The findings indicate that the training has a positive and significant effect on empowerment, thereby proving the essential role of the Rumah BUMN training program in improving skills, independence, and welfare among housewives.